2007
DOI: 10.1097/pec.0b013e318030083d
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric and Neonatal Transport Teams With and Without a Physician

Abstract: Outcomes for the 2 types of teams were equivalent. Nonphysician teams responded more quickly and spent less time at the referring facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…Interestingly, during this study period our center was transitioning to a specialized nurse-led transport team. Over the last decade several studies have demonstrated that specialized teams improve outcomes whether led by specially trained nurses or physicians 2123 . However, having an objective tool to assist with triage decisions previously made by the physician-led team may become more valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, during this study period our center was transitioning to a specialized nurse-led transport team. Over the last decade several studies have demonstrated that specialized teams improve outcomes whether led by specially trained nurses or physicians 2123 . However, having an objective tool to assist with triage decisions previously made by the physician-led team may become more valuable.…”
Section: Discussionmentioning
confidence: 99%
“…2 Since then, research has increased and led to several publications relevant to clinical practice and improving the quality of care provided during transport. [9][10][11][12][13][14][15][16] The broad diversity of, practice differences, and geography served by programs across the United States continues to challenge collaborative research efforts. An organized transport research network designed to answer relevant clinical questions in a multicentered collaborative fashion is urgently needed.…”
Section: Clinical Researchmentioning
confidence: 99%
“…Several studies have evaluated equipment and efficacy of therapeutic interventions. [13][14][15][16] In addition, the first prospective, randomized clinical trial in pediatric interfacility transport was recently published, illustrating the need for enhanced monitoring and timely resuscitation of critically ill transport patients. 16 It also demonstrated the ability to conduct clinical trials in the transport environment, even with informed consent requirements and concerns.…”
Section: Clinical Researchmentioning
confidence: 99%
“…Despite the ability to provide more efficient medical command, scene times and overall transport times may be longer with physician presence. 18 Additional clinical expertise and advanced procedural capabilities give physicians a distinct skill set; however, because these skills are required so infrequently, it is difficult to determine which calls require physician presence. In a series of 166 pediatric transports with physicians in Alabama, only 9% had procedures performed requiring a physician, and in 43% of calls, the physician was thought to be noncontributory.…”
Section: Physiciansmentioning
confidence: 99%